2019
DOI: 10.1186/s13643-019-1039-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of whey protein supplements on the serum levels of amino acid, creatinine kinase and myoglobin of athletes: a systematic review and meta-analysis

Abstract: Background Consuming whey protein supplements, along with physiotherapy and psychotherapy, have been recognised in sports performance. Whey protein supplements (WPS) is one of the commonly used supplements as ergogenic aids for athletes to enhance their muscle performance and recovery during sport-related injuries. The purpose of this systematic review is to investigate the effectiveness of WPS over the blood biochemistry mainly amino acids, creatinine kinase and myoglobin which influence performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 47 publications
0
13
0
5
Order By: Relevance
“…Whey protein, having a high availability of BCAAs, has been investigated for its efficiency in stimulating muscle protein synthesis [15,18,19]. However, previous meta-analyses demonstrated small to moderate effects of whey protein on muscle function during the temporal recovery from <24 to 96 h after resistance exercise [46], and a reduction of myoglobin and CK levels considering different form of exercises [47]. However, whey protein failed to reduce CK and muscle soreness during recovery until 96 h, either as a pre-or post-exercise supplementation during eccentric isokinetic contractions [48].…”
Section: Discussionmentioning
confidence: 99%
“…Whey protein, having a high availability of BCAAs, has been investigated for its efficiency in stimulating muscle protein synthesis [15,18,19]. However, previous meta-analyses demonstrated small to moderate effects of whey protein on muscle function during the temporal recovery from <24 to 96 h after resistance exercise [46], and a reduction of myoglobin and CK levels considering different form of exercises [47]. However, whey protein failed to reduce CK and muscle soreness during recovery until 96 h, either as a pre-or post-exercise supplementation during eccentric isokinetic contractions [48].…”
Section: Discussionmentioning
confidence: 99%
“…Lam et al reported that whey protein supplements (WPS) had significantly overall increased the level of branched-chain amino acids level by 458.57 nmol/L (CI = 179.96, 737.18; I 2 = 100 %; p = 0.00) and level of essential amino acids by 624.03 nmol/L (CI = 169.27, 1078.8; I 2 = 100 %; p = 0.00) compared to the control group, wherejbas WPS had decreased myoglobin level by 11.74 ng/ml (CI = -30.24, 6.76; I 2 = 79.6 %; p = 0.007) and creatinine kinase level by 47.05 U/L (CI = -129.47, 35.37; I 2 = 98.4 %; p = 0.000) [18]. Recently, Carlsson et al demonstrated their success in production of human myoglobin, a heme-protein in muscle with important functions in tissue oxygenation and as a regulator in nitric oxide signaling from the leaves of Nicotiana benthamiana by transient expression using a viral vector delivered by Agrobacterium tumefaciens [19].…”
mentioning
confidence: 87%
“…Following damage to myocardial tissue, cTnI can quickly enter the blood system, causing the cTnI content in the blood to increase; therefore, the level changes of cTnI can reflect the degree of myocardial damage (16). Mb is a small molecule pigment-protein formed by the combination of globin and methemoglobin that is mainly distributed in the myocardium and striated muscle cells and has the function of transporting and storing oxygen in muscle cells (17). When cardiomyocytes are damaged, Mb carries out blood circulation from the cardiomyocytes through diffusion.…”
Section: A B Cmentioning
confidence: 99%